Pengaruh Kinerja Lingkungan, Pengungkapan Tanggung Jawab Sosial Perusahaan terhadap Profitabilitas Perusahaan dengan Ukuran Perusahaan sebagai Variabel Moderasi - Twindita, Maristia Fitri (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
This study aims to examine the influence of environmental performance and corporate social responsibility disclosure on profitability with firm size as a moderating variable. 12 company samples are selected through purposive method toward the population of mining companies listed in the Indonesia Stock Exchange and registered as the PROPER participants for 4 years from 2011 until 2014. The result of the study shows that environmental performance does not affect profitability but corporate social responsibility disclosure influences it. Meanwhile, the firm size can strengthen neither the relationship between the environmental performance and profitability nor the correlation between corporate social responsibility and profitability.Keywords: Environmental performance; Corporate social responsibility disclosure; Profitability; Firm Size